A novel approach for cognitive radio application in 2.4-GHz ISM band. Issue 5 (4th May 2017) - Das, Deepa; Das, Susmita
ABSTRACT: This paper reveals the issues of incorporating the cognitive radio (CR) technology in the 2.4-GHz industrial, scientific and medical band. The objective of allowing the coexisting systems in this unlicensed band is to opportunistically share the underutilised spectrum so as to improve the spectral usages efficiency. Hence, proper evaluation of the spectrum occupancy is one of the important tasks. Therefore, we adopt a double threshold-based detection scheme to differentiate the sub-bands with respect to their occupancy statistics satisfying the target miss detection probability. Further, an adaptive power allocation to the CR user (CRU) is proposed for maximising the system throughput under the constraints of interference to the co-existing systems and maximum transmission power. We consider path loss in the channel modelling between the CRUs. Our proposed approach is investigated over the real measurement data collected in the Swearingen Engineering Center, University of South Carolina, Columbia, SC, USA.